Screening for developmental delay at 18 months using the Infant Toddler Checklist: A validation study. - Cornelia M Borkhoff; Haris Imsirovic; Imaan Bayoumi; Colin Macarthur; Kimberly M Nurse; Teresa To; Mark E Feldman; Eddy Lau; Braden Knight; Catherine S Birken; Jonathon L Maguire; Patricia C Parkin (PLoS ONE)
Objective The Infant Toddler Checklist (ITC) may be promising as a single tool at the 18-month visit to detect a range of developmental concerns. We examined the predictive validity of the ITC; and the association between positive ITC screening and health care utilization (HCU). Methods Prospective cohort study of children at average-risk for developmental delay attending their 18-month visit in primary care in Toronto, Canada. Parents completed the ITC. HCU from the single-payer provincial health system was collected from health administrative databases ensuring complete follow-up. Physician billing code for a neurodevelopmental consultation was the primary outcome and criterion measure. Six other HCU types were assessed. Results Of 1460 children with a mean age at screening of 18 months, 11% screened ITC positive. Mean age at follow-up was 8 years, 2.6% had a neurodevelopmental consultation. Screening test properties (with neurodevelopmental consultation as the criterion measure): 40% sensitivity (95% CI 24%, 57%), 90% specificity (95% CI 88%, 91%), 10% false positive rate (95% CI 9%, 12%). Using multivariable negative binomial regression, a positive ITC was associated with higher rates of 6 of 7 HCU types, including neurodevelopmental consultation (aRR 2.78, 95% CI 1.37, 5.67, p = 0.005). Conclusion The ITC had high specificity and a low false positive rate, suggesting that most children with a negative ITC will not have a later neurodevelopmental consultation, and use of the tool may minimize unintended harms such as anxiety and resource use. The low sensitivity highlights the importance of ongoing developmental surveillance. Low sensitivity of other screening tools is discussed.